Effects of Bacillus velezensis GUAL210 control on edible rose black spot disease and soil fungal community structure - Dong, Wanpeng; Long, Ting; Ma, Jinghua; Wu, Nan; Mo, Weidi; Zhou, Zhicheng; Jin, Jing; Zhou, Hongying; Ding, Haixia (Frontiers in Microbiology, 2023)
Introduction Rose black spot is an economically important disease that significantly decreases flower yield. Fungicide and biological control are effective approaches for controlling rose black spot. The objective of this study was to evaluate the effect of application of biological and chemical control agents, including Bacillus velezensis (GUAL210), Bacillus sp. (LKW) and fungicide (CP) on the black spot disease and rhizosphere fungal community structure of edible rose. Methods In this study, the R. chinensis ‘Crimson Glory' was taken as the research object, and the field experiment was designed by randomized block design. The experiment contained 3 treatments (CP, GUAL210, LKW) and 1 control. The control effect and growth promoting effect of fungicide and biological control on rose black spot were compared. The composition and diversity of rhizosphere soil fungal community of different treatments of rose were studied by high-throughput sequencing method. The fungal community composition, correlation of environmental factors and differences in metabolic pathways related to rose disease were analyzed, and the correlation between rhizosphere soil fungal community of rose and biological control of disease was explored. Results and discussion Both disease incidence and disease index differed significantly among groups (LKW < GUAL210 < CP < CK), and disease control effect exhibited no significant difference between GUAL210 and LKW (60.96% and 63.86%, respectively). Biological control was superior to chemical control in terms of disease prevention effects and duration, and it significantly increased the number of branches and flowers of rose plants. Ascomycota and Basidiomycota accounted for more than 74% of the total fungal abundance, and the abundance of Ascomycota was highest in CK, followed by GUAL210, CP and LKW, which was consistent with the disease occurrence in each group. The analysis of metabolic pathways showed that the HSERMETANA-PWY in each experimental group was significantly lower than that in control group. The Shannon index in each experimental group was significantly lower than that in control group. PCoA analysis showed that the rhizosphere fungal community structure in each experimental group was significantly different from that in control group. Trichoderma, Paraphaeosphaeria, Suillus, Umbelopsis in GUAL210, and Galerina in LKW replaced Mortierella, Pestalotiopsis, Ustilaginoidea, Paraconiothyrium, Fusarium, and Alternaria as dominant flora, and played a nonneglectable role in reducing disease occurrence. The difference in rhizosphere fungal community structure had an important impact on the incidence of rose black spot disease. Biological control is crucial for establishing environment-friendly ecological agriculture. GUAL210 has promising prospects for application and development, and may be a good substitute for chemical control agents.